2002
DOI: 10.1159/000047762
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Hospitalized Patients: Are There Special Risk Factors?

Abstract: Background and Purpose: The occurrence of stroke in patients hospitalized for various illnesses remains a particular challenge for neurologists. Determining the potential causes for these particular cerebrovascular events may help to define the population at risk and to take measures in order to prevent stroke during hospitalization. The aim of our study was to evaluate the potential risk factors associated with stroke, which occurred in patients hospitalized for other illnesses. Methods: This retrospective ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 24 publications
1
47
0
2
Order By: Relevance
“…Compared to out-of-hospital stroke (OHS), cases of IHS are more likely to have an ischemic mechanism and are more likely to be embolic in origin [2, 12]. The spectrum of risk factors also differs for IHS cases; factors such as cerebrovascular stenosis [12, 13], atrial fibrillation [14,15,16], remote as well as recent myocardial infarction [14, 17], and elevated or unstable blood pressure [18], have all been reported to occur more frequently in cases with IHS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to out-of-hospital stroke (OHS), cases of IHS are more likely to have an ischemic mechanism and are more likely to be embolic in origin [2, 12]. The spectrum of risk factors also differs for IHS cases; factors such as cerebrovascular stenosis [12, 13], atrial fibrillation [14,15,16], remote as well as recent myocardial infarction [14, 17], and elevated or unstable blood pressure [18], have all been reported to occur more frequently in cases with IHS.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies on this topic are based on a small numbers of stroke cases, are limited to a small number of hospitals, or tend to focus on one particular aspect such as time of evaluation [3], stroke mechanism [2], risk factors [18], or outcomes [14]. In this study we describe a large case series of IHS cases that were identified as part of a representative statewide prospective hospital-based acute stroke registry.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, fever has been found to be an independent risk factor for developing in-hospital stroke. 8 Previous studies have identified an infectious cause in 40% to 80% of poststroke patients with fever 3,7,9 ; the rest are of unknown etiology, and some are presumed to have a central cause. 2,10 Despite the evidence of poor poststroke outcomes with fever, little is known about the epidemiology of fever after stroke, or to what extent the severity of fever affects outcomes.…”
mentioning
confidence: 99%
“…Second, a majority of hypernatremic patients are dehydrated. Studies have shown that dehydration is risk factor for ischemic stroke [26,27] because it can reduce cerebral blood flow and then precipitate in ischemic stroke and even result in sympathetic system activation, triggering the coagulation cascade [28]. However, the difference between hyponatremic and hypernatremic patients for the risk of stroke may be needed to further clarify in the future.…”
Section: Discussionmentioning
confidence: 99%